2012
DOI: 10.1021/ja300527w
|View full text |Cite
|
Sign up to set email alerts
|

Lyotropic Smectic B Phase Formed in Suspensions of Charged Colloidal Platelets

Abstract: Here, we present the first observation of a smectic B (Sm B ) phase in a system of charged colloidal gibbsite platelets suspended in dimethyl sulfoxide (DMSO). The use of DMSO, a polar aprotic solvent, leads to a long range of the electrostatic Coulomb repulsion between platelets. We believe this to be responsible for the formation of the layered liquid crystalline phase consisting of hexagonally ordered particles, that is, the Sm B phase. We support our finding by highresolution X-ray scattering experiments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 46 publications
2
34
1
1
Order By: Relevance
“…Recently, high-quality computer simulations on systems of charged colloidal platelets have been reported [63], which support the transitions from a discotic nematic phase (N D ), via a columnar nematic (N C ) to a columnar phase (C). However, the SmB phase observed by Kleshchanok et al [62] was not detected in these simulations. …”
Section: Colloidal Silica Rodscontrasting
confidence: 63%
“…Recently, high-quality computer simulations on systems of charged colloidal platelets have been reported [63], which support the transitions from a discotic nematic phase (N D ), via a columnar nematic (N C ) to a columnar phase (C). However, the SmB phase observed by Kleshchanok et al [62] was not detected in these simulations. …”
Section: Colloidal Silica Rodscontrasting
confidence: 63%
“…Recently, also a smectic B phase has been reported for suspensions of Gibbsite platelets. 9 For the Gibbsite suspensions it was found that on a microscopic level the formation of the nematic phase is preceded by the formation of nematic droplets (tactoids) in the isotropic phase. Finally these tactoids coalesce at sufficiently high concentrations to a nematic phase on a macroscopic scale.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, SAXS experiments revealed that the nematic phases at high salt concentrations or low platelet concentrations are of the usual (discotic) nematic type, while those at low salt/high platelet concentrations are of the columnar nematic (N C ) type, where increased lateral correlations indicate the formation of stacks of platelets. Kleshchanok et al [39] dispersed charged gibbsite platelets in dimethyl sulfoxide (DMSO), a polar aprotic solvent leading to a long range of the electrostatic Coulomb repulsion between platelets, and did report a smectic-B, a layered liquid-crystalline phase consisting of hexagonally ordered particles (without inter-layer correlations).…”
Section: Plate-like Particlesmentioning
confidence: 99%